Answer:
C. 8x - 16
D.
+ 6x + 8
A. 2 (x + 3)
B. 7(2 - x)
C. -8x
D. 7x
Explanation:
c.
To solve this problem, first, one must distribute, multiply every term inside the parenthesis by the term outside,
2(4x - 8)
=(2)(4x) + (2)(-8)
= 8x - 16
d.
To solve this problem, distribute, multiply every term inside one parenthesis by every term in the other, the combine like terms,
(x + 4)(x + 2)
= (x)(x) + (4)(x) + (2)(x) + (4)(2)
=
+ 4x + 2x + 8
=
+ 6x + 8
a.
Factor, write the given expression as the product of two expressions. Take out a common factor that both terms have,
2x + 6
= 2(x + 3)
b.
Factor this expression, take out a common factor, and rewrite the expression as the product of two other expressions,
14 - 7x
7(2 - x)
c.
Combine like terms,
2x - 10x
= -8x
d.
Combine like terms to solve this problem
3x + 4x
= 7x